August Wilhelm Ambros, Musikaufsätze und -rezensionen 1872-1876, Bd. 1: 1872 und 1873 - Štědronská, Markéta (1a0d3eb9-6857-41e9-815e-2187cfa716ee, 2017)
The present edition of musical essays and reviews by August Wilhelm Ambros (1816-1876) covers the years 1872-1876-a time that Ambros spent as a music reviewer for the Wiener Zeitung in Vienna. The first volume contains, in total, 138 essays from the years 1872 and 1873. It documents not only Ambros' position within Viennese music criticism of the 1870s, but also an important chapter in European musical history.